Pengujian Hexagon Fraud Theory dalam Mendeteksi Fraudulent Laporan Keuangan - Sari, Yohana Veny Pradita; Akadiati, Victoria Ari Palma; Estisari, Kristina (Universitas Batanghari Jambi, 2024)
This research aims to test the fraud hexagon component for the possibility of fraudulent financial reports. The research population uses companies listed on the Indonesia Stock Exchange with a sample of 32 banking issuers. The research results show that only the change in director variable has a positive influence on fraudulent financial reports. The financial stability variable, the external auditor quality variable, the change of auditor variable, the CEO's picture variable, the project variable with the government are not proven to have an effect on fraudulent financial reports.